Strategi Pemasaran Politik Dewan Pimpinan Daerah Partai Golkar Kabupaten Kotawaringin Barat untuk Pemilu 2024 - Ricky Zulfauzan; Andrie Wahyu Saputra Untung (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
Political marketing is crucial in shaping voter preferences and influencing electoral outcomes. This study analyzes the political marketing strategies employed by the Regional Leadership Council (Dewan Perwakilan Daerah or DPD) of the Golkar Party in West Kotawaringin to secure public support in the 2024 General Election. Using a qualitative case study approach, this research collects primary data through in-depth interviews with party officials, campaign strategists, and community figures. In contrast, secondary data is obtained from policy documents, media reports, and academic literature. The findings indicate that Golkar implements a multi-dimensional political marketing strategy, which includes (1) digital political communication, leveraging social media and targeted outreach to engage with voters; (2) grassroots engagement, involving direct community interaction and public service programs; (3) strategic coalition-building, forming alliances with local organizations and influential figures; and (4) resource optimization, utilizing financial assets, infrastructure, and political networks effectively. Additionally, this study identifies key factors that influence Golkar’s campaign effectiveness, including candidate branding, party credibility, policy relevance, and message consistency. The findings contribute to political marketing literature by illustrating how regional parties adapt their strategies in local elections while offering practical insights for enhancing voter engagement and campaign effectiveness.